Analysis of the Maqāṣid al-Qur’an Wasfī ‘Ashyur (Maqāṣid al-Suwar) in Fī Ẓilāl al-Qur’an - Nabila Indah Dwi Ariani; Nadya Putri Prameswari; Abd. Kholid (Journal of Ulumul Qur'an and Tafsir Studies, 2025)
This article examines the maqāṣidī (purpose-based) approach to interpretation in Sayyid Quthb's work Fī Ẓilāl al-Qur’ān, and relates it to Waṣfī ‘Āsyūr Abū Zayd's theory of maqāṣid al-Qur’an. Through comparative analysis, this article highlights how Sayyid Quthb directs his interpretation toward the essential values and primary objectives that the Qur’an seeks to achieve, rather than on narrative or speculative details that are irrelevant to the spiritual and moral purposes of the text. His approach aligns with the structure of maqāṣid suwar as explained by Waṣfī ‘Āsyūr, which involves dividing the surah into thematic units that lead to a single primary objective, while avoiding discussions not directly indicated by the text. This article demonstrates that Sayyid Quthb applies a consistent interpretive framework, focusing on personal and social transformation, and emphasizing spiritual values such as murāqabah and khasyyah as the fruits of a deep understanding of the Qur'an. Thus, Fī Ẓilāl al-Qur’ān can be positioned as a practical example of the application of maqāṣidī tafsir, which has made an important contribution to the modern tafsir tradition.